HUBUNGAN ANTARA CITRA DIRI DENGAN SIKAP TERHADAP â€œSELFIEâ€ PADA MAHASISWA - Herlinda Dewi Astuti; Indriyati Eko Purwaningsih (Universitas Sarjanawiyata Tamansiswa, 2015)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â The aims of this research are for knowing the relation between self-image and â€œselfiesâ€ attitude to students of Sarjanawiyata Tamansiswa University in Faculty of Psychology and for knowing how big the self-image role towards â€œselfiesâ€ attitude.Â Â Â Â Â Â Â Â Â Â Â The subjects of this research were 18-23 years old female of Psychology Faculty from academic year 2009 until 2014. The sampling taking technique is used by Purposive Sampling technique. The data analysis method used in this research was Product Moment Correlation.Â Â Â Â Â Â Â Â Â Â Â The results from data analysis of self-image variable towards â€œselfiesâ€ attitude showed that the value r 0,322 with p = 0,001 (p < 0,05). Based on those results of correlations, it stated that were significant positive relations between self-image and â€œselfiesâ€ attitude to students of Sarjanawiyata Tamansiswa University in Faculty of Psychology. It means that, the effectives impact of self-image towards â€œselfiesâ€ attitude were 10,4%. This was also showed that 89,6% â€œselfiesâ€ attitude determined by the others influencing factors.Â Keywords: Self-image, Attitude, Selfie